2009
DOI: 10.1583/09-2735.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open and Endovascular Repair of Ruptured Abdominal Aortic Aneurysms From the ACS-NSQIP 2005–07

Abstract: Purpose: To compare endovascular (EVAR) and open surgical repair (OSR) for ruptured abdominal aortic aneurysms (RAAA) in terms of preoperative hemodynamic status and comorbidities. Methods: The 2005 to 2007 American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database was interrogated to find all patients undergoing repair for RAAA. Of the 567 RAAA repairs identified, 121 (21%) were endovascular and 446 (79%) were open. Demographics, comorbidities, and preoperative hemodynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…As a result, preventing AKI is crucial in improving outcome, especially in populations at high-risk, such as those undergoing EVAR. The predictive factors of AKI after elective EVAR are not well determined, as the randomized studies have not reported AKI-incidence and the majority of case-series have not used a consistent AKI definition (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, preventing AKI is crucial in improving outcome, especially in populations at high-risk, such as those undergoing EVAR. The predictive factors of AKI after elective EVAR are not well determined, as the randomized studies have not reported AKI-incidence and the majority of case-series have not used a consistent AKI definition (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many observational studies point favorable outcomes for EVAR when compared to OR, these were not reproduced in the major RCTs. [13][14][15][17][18][19][20] Intuitively, the low-invasive profile makes EVAR particularly appealing for rAAA patients: treatment under local anesthesia with lower associated hypotension are more suitable for bleeding patients. Additionally, there is a reduced procedural risk for elderly comorbid patients, usually not considered for open repair.…”
Section: Discussionmentioning
confidence: 99%
“…While no differences on inhospital mortality was found on the first, all the four observational studies included presented lower in-hospital mortality for EVAR. [13][14][15][16][17]19,20 Additionally, lower post-operative complications and shorter stay is also reported for EVAR both in RCT and administrative registries. [15][16][17][18][19] For this reason, it is difficult to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations